(untitled) (Research, Society and Development, 2021)
Objective: The clinical case describes the presence of a supernumerary tooth located between the upper incisors in a pediatric male patient, aged 9 years and 5 months. Methodology: Based on the patient’s permission through the Informed Consent Form (FICF) to share her image for the proper purpose, this study is a clinical case report of a descriptive analytical nature (Pereira et al., 2018). Clinical Case Report: Male patient, JVSD, 9 years and 5 months old, attended the children’s dental clinic at Centro Universitário Fametro (CEUNI) for clinical evaluation during the anamnesis, the responsible person reported that the main complaint was that the child had one more tooth in his mouth. Denied painful sensation in the region, as well as bleeding. Final Considerations: The clinical case showed the importance of anamnesis, clinical and imaging examination to conclude a good diagnosis and treatment plan, culminating in clinical success.